2019
DOI: 10.1016/j.cherd.2019.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Production of levulinic acid from glucose in sulfolane/water mixtures

Abstract: Levulinic acid derived from biomass is a versatile platform molecule, which can be used in manufacturing different compounds to replace fossil-based chemicals. In this study, the effect of sulfolane as solvent in sulphuric acid catalysed levulinic acid production from glucose was investigated. The broad sulfolane concentration range was systematically studied and a kinetic model was developed to describe the levulinic acid production. A significant increase in glucose conversion rate was observed when the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The latter showed a highly selective route to produce LA from straw, resulting in an LA yieldof up to 96.6 mol% (21.6 wt%). Mikola et al 57 investigated the effect of sulfolane as solvent on LA production from glucose using sulfuric acid as the catalyst. The results showed that the maximum yield selectivity of LA was slightly over 50% and independent of the solvent composition.…”
Section: Furfuralcohol Catalytic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The latter showed a highly selective route to produce LA from straw, resulting in an LA yieldof up to 96.6 mol% (21.6 wt%). Mikola et al 57 investigated the effect of sulfolane as solvent on LA production from glucose using sulfuric acid as the catalyst. The results showed that the maximum yield selectivity of LA was slightly over 50% and independent of the solvent composition.…”
Section: Furfuralcohol Catalytic Hydrolysismentioning
confidence: 99%
“…The latter showed a highly selective route to produce LA from straw, resulting in an LA yieldof up to 96.6 mol% (21.6 wt%). Mikola et al 57 . investigated the effect of sulfolane as solvent on LA production from glucose using sulfuric acid as the catalyst.…”
Section: Preparation and Separation Of Lamentioning
confidence: 99%
“…HMF has a furan ring‐structured system that consists of hydroxymethyl 5 and formyl functional groups 6 . HMF, which is also named 5‐(hydroxymethyl)‐2‐furaldehyde, 7 can be derived from the carbohydrate conversion of glucose, cellulose, and fructose, 8 which is further converted into 2,5‐furandicarboxylicacid (FDCA), 9 levulinicacid, 10 formicacid, 11 and 2,5‐dimethylfuran (DMF), 12 and other chemicals (Figure 1), which can be used in various applications, 13 such as fine chemicals, solvents, biofuel precursor, polymers, and pharmaceuticals 14 . Typically, HMF can be synthesized from lignocellulosic biomass via a series of complex processes, including the pretreatment of biomass, which is then hydrolyzed to glucose, isomerization of glucose to fructose, and dehydration of fructose to HMF by BrĂžnsted acid 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Research into utilizing waste biomass has attracted great attention all over the world to produce different biobased products and sustainable energy infrastructure. , Lignocellulosic biomass consists of mainly three parts: lignin, hemicellulose, and cellulose. , However, the biomass composition may vary with the source and area. Typically, biomass consists of 75% carbohydrates in the form of hemicelluloses and celluloses, consisting primarily of C 5 and C 6 sugars, respectively. , It has been noted that among the biomass components, cellulose and hemicellulose can more easily be converted into useful chemical components as compared to lignin …”
Section: Introductionmentioning
confidence: 99%